The labor insertion of professionals with a doctorate in Social Sciences in Argentina. - Emiliozzi, sergio (Instituto de Investigaciones Socioeconómicas, 2021)
This paper presents a preliminary analysis of a research project`s results on the labor insertion of professionals with a doctorate in Social Sciences in Argentina. The interest in the labor insertion of doctors has been gaining relevance in studies on public policies in science and technology. It is intended to relieve here, in the first place, the public policy developed to employ doctors, as well as the main features of the system. Then, the data arising from the survey will be analyzed, which will allow to survey the most salient edges of the so-called labor market of professionals with doctorates in the area of ​​Social Sciences. Finally, it will conclude with suggestions so that public policy can resolve the difficulties that the labor market presents for doctorates in Social Sciences.